The 'feminine' entrepreneurial personality trait: The competitive advantage of female college-student entrepreneurs in Chinese wei-shang businesses?. Issue 5 (December 2016) - Ng, Jhony; Huang, Metis; Liu, Yiping
Abstract We conducted this grounded theory research to study the motivation ofwei -shangs (i.e., wechat businesspersons) in starting their own business ventures, and their business model and entrepreneurial behaviors. We found that many college-studentwei -shangs are risk-adverse individuals who think of entrepreneurship merely as a leisure-time pursuit. We also found that 'feminine' characteristics seem to hold a key to successful entrepreneurship. Furthermore, we found thatwei -shangs use thewechat platform to extend their social network and to gain the trust of potential customers to get them to buy their products.